2016
DOI: 10.1111/jnu.12214
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With a Family‐Focused Intervention for Mild Cognitive Impairment Dyads

Abstract: Purpose This paper describes satisfaction that persons with MCI (PwMCI) and their caregivers had with the Daily Enhancement of Meaningful Activity (DEMA) intervention. Methods This randomized controlled pilot study compared satisfaction (usefulness, ease of use, and acceptability) with DEMA (n =17 dyads) to an information support (IS) control group (n=19 dyads). Six bi-weekly sessions (2 in-person and 4 telephone) were delivered by trained nurses. Data analysis included descriptive statistics, independent-sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…In our participants, the dyadic effects improved the life satisfaction even for those stroke survivors who did not participate in the therapy program (in G 2 ). However, our findings do not agree with the work of Lu and colleagues, who found that a family‐focused intervention only improved the life satisfaction of stroke survivors with dementia and did not improve the caregivers' life satisfaction. Our inclusion of the stroke survivors with their spouse caregivers in the therapy program not only improved the caregivers' outcomes but also enhanced the care recipients' positive outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…In our participants, the dyadic effects improved the life satisfaction even for those stroke survivors who did not participate in the therapy program (in G 2 ). However, our findings do not agree with the work of Lu and colleagues, who found that a family‐focused intervention only improved the life satisfaction of stroke survivors with dementia and did not improve the caregivers' life satisfaction. Our inclusion of the stroke survivors with their spouse caregivers in the therapy program not only improved the caregivers' outcomes but also enhanced the care recipients' positive outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…However, as described in the introduction, initial evidence has been gathered showing a potential link between engagement in meaningful activities and parental and child health and wellbeing [ 23 , 24 , 45 ]. Moreover, the therapeutic use of meaningful activities has been found to improve patient and caregiver health and wellbeing [ 46 , 47 ]. Considering the potentially favorable effect of parents’ various meaningful activities on their preterm infants’ health and wellbeing, such activities could be clinically relevant in the context of neonatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, interventions focused on maintaining and improving interpersonal relationships and communication among patients with dementia and mild cognitive impairment have been shown to improve quality of life and reduce caregiver burden. 3 Second, memory training and cognitive behavior therapy have been found to improve overall cognitive functioning in patients with mild cognitive impairment. 4 Third, organized exercise programs in patients with dementia or mild cognitive impairment can improve both cognitive and physical functioning.…”
Section: Discussionmentioning
confidence: 99%